2016
DOI: 10.2196/jmir.5065
|View full text |Cite
|
Sign up to set email alerts
|

Online Health Information-Seeking Behavior and Confidence in Filling Out Online Forms Among Latinos: A Cross-Sectional Analysis of the California Health Interview Survey, 2011-2012

Abstract: BackgroundHealth information is increasingly being disseminated online, but there is a knowledge gap between Latinos and non-Hispanic whites, particularly those whose English language proficiency is poor, in terms both of online health information-seeking behavior and computer literacy skills. This knowledge gap may also exist between US- and foreign-born Latinos.ObjectiveThe specific aim of this study was to examine Internet use, online health information-seeking behavior, and confidence in filling out online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 27 publications
(42 reference statements)
5
55
0
Order By: Relevance
“…[26] Our post-hoc analysis of the Mexican-identified subpopulation shows that nativity also matters within Latinos groups, which is in line with other studies that use Spanish as a measures of acculturation, [3,26] and with previous state-level studies showing differences between US and foreign-born Latinos. [7] Additionally, the fact that age did not significantly affect all channels of online HISB and HIT within Mexican-identified populations bolsters previous findings where age was not related to online HISB. [15] Future research should examine which online applications, programs and services are being used, especially by foreign-born Latinos and the Mexican-identified population.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…[26] Our post-hoc analysis of the Mexican-identified subpopulation shows that nativity also matters within Latinos groups, which is in line with other studies that use Spanish as a measures of acculturation, [3,26] and with previous state-level studies showing differences between US and foreign-born Latinos. [7] Additionally, the fact that age did not significantly affect all channels of online HISB and HIT within Mexican-identified populations bolsters previous findings where age was not related to online HISB. [15] Future research should examine which online applications, programs and services are being used, especially by foreign-born Latinos and the Mexican-identified population.…”
Section: Resultsmentioning
confidence: 62%
“…Latino Subgroup Affiliation by Nativity There are differences between US and foreign-born Hispanics with regards to the age structure and language use within the population. [7,23,24] Additionally, studies have shown significant behavioral and health differences between various Hispanic ethnic groups.…”
Section: Primary Outcomesmentioning
confidence: 99%
See 3 more Smart Citations